Frequency of the necessity of dentoalveolar surgery or conservative treatment in patients before kidney transplantation depending on the duration of dialysis and causative nephrological disease - Möst, Tobias; Lutz, Rainer; Jahn, Arne Eric; Heller, Katharina M.; Schiffer, Mario; Adler, Werner; Deschner, James; Weber, Manuel; Kesting, Marco Rainer (Clinical Oral Investigations, 2021)
Objectives: This retrospective study evaluates intraoral surgical and conservative treatment need in patients with a chronic kidney end-stage disease, depending on the duration of dialysis treatment and the causative nephrological disease. Material and methods: This study is based on data of patients referred to the Department of Oral and Maxillofacial Surgery of the University Hospital Erlangen, Germany, prior to kidney transplantation between January 2015 and March 2020. The necessity for oral surgical or dental therapy was determined by clinical and radiological examinations. Data on renal replacement therapy, cause of underlying renal disease, lifestyle, and general health were collected. Results: Data of N = 89 patients demonstrated that surgical treatment need depends on dialysis duration (p = 0.042). Patients, who had been dialyzing for 2 to 3 years showed the highest need for surgical intervention (80.0%; p = 0.024), followed by dialysis patients with a dialysis time of more than 3 years (48.1%). Similarly, dialysis patients in the second or third year of dialysis had the highest need for conservative treatment (73.3%; p > 0.05), followed by 55.6% of dialysis patients in the third year of dialysis. Conclusions: Operative and conservative treatment is essential to optimize subsequent kidney transplantation. The greatest necessity could be detected for patients in the second and third years of dialysis. Clinical relevance: Oral health addressing surgical and conservative treatment need depends on the duration of dialysis in patients with a chronic kidney end-stage disease.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Immunosuppression; Kidney; Oral health; Organ transplantation